IL-13 and idiopathic pulmonary fibrosis: Possible links and new therapeutic strategies. (August 2017) - Passalacqua, Giovanni; Mincarini, Marcello; Colombo, Daniele; Troisi, Giuseppe; Ferrari, Marta; Bagnasco, Diego; Balbi, Francesco; Riccio, Annamaria; Canonica, Giorgio Walter
Abstract: The recent advances in the knowledge of immunological aspects of many pulmonary diseases, allowed to identify cells, biological functions, cytokines, and receptors that are preferentially involved in each disease. This is the case of asthma, where IL-13 (together with IL-4) is recognized as a central mediator. The role of IL-13 is strictly related, via complex signaling pathways, to eosinophil recruitment and activation, to mucus secretion, periostin generation and to fibrogenic processes (which are part of the remodeling process). These peculiar roles of IL-13 have suggested the hypothesis of its role in Idiopathic Pulmonary Fibrosis, and consequently of its antagonists in the treatment of such disease. We review herein the immunological roles of IL-13 in asthma and IPF, and the currently ongoing attempts to treat IPF by IL-13 antagonism strategies.